Recreational landscape perception and pro-environmental behavior: the mediating roles of place identity and pro-environmental behavioral spillover - Zhang, Ke (Frontiers in Psychology, 2025)
IntroductionTourism significantly contributes to global economies but also intensifies environmental pressures at destinations. Promoting tourists’ pro-environmental behavior (PEB) is therefore crucial for sustainable tourism. Recreational landscape perception (RLP), a multidimensional and integrative concept, may shape visitors’ emotional connections and subsequent behaviors. However, few studies have examined its combined effects on both place-specific and general PEB, or the underlying psychological pathways. This study applies the Stimulus-Organism-Response (S-O-R) model to investigate how RLP influences PEB through place identity and behavioral spillover.MethodsA visitor survey was conducted in Langya Mountain National Forest Park during peak season, yielding 457 valid responses. Recreational landscape perception, place identity, and both place-specific and general PEB were measured using established Likert scales. Structural equation modeling with bootstrapping was applied to test the proposed relationships and mediation effects.ResultsThe results showed that: (a) RLP significantly and positively influences place-specific PEB through place identity; (b) RLP significantly and positively influences general PEB through place identity; and (c) RLP significantly and positively influences general PEB through both place identity and place-specific PEB.DiscussionThe findings demonstrate that RLP, as a multidimensional perception of destination landscapes, significantly enhances both place-specific and general PEB, with place identity and behavioral spillover acting as key mediators. Theoretically, this study advances the S-O-R framework by integrating natural, cultural, and experiential dimensions of landscape perception into a unified model, and by empirically validating the dual mediation pathway from destination-specific experiences to broader environmental actions. Practically, the results offer evidence-based guidance for sustainable tourism planning-highlighting that enhancing visitors’ holistic landscape experiences can strengthen emotional bonds, stimulate on-site conservation behaviors, and encourage the adoption of eco-friendly habits in daily life.